2022
DOI: 10.1093/jmammal/gyac016
|View full text |Cite
|
Sign up to set email alerts
|

Estimating deer density and abundance using spatial mark–resight models with camera trap data

Abstract: Globally, many wild deer populations are actively studied or managed for conservation, hunting, or damage mitigation purposes. These studies require reliable estimates of population state parameters, such as density or abundance, with a level of precision that is fit for purpose. Such estimates can be difficult to attain for many populations that occur in situations that are poorly suited to common survey methods. We evaluated the utility of combining camera trap survey data, in which a small proportion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
(81 reference statements)
1
10
0
Order By: Relevance
“…We found that sambar deer activity decreased in the treatment area relative to the non-treatment area. Detection rates of deer on camera traps were positively correlated with deer densities estimated using spatial mark-resight models for white-tailed deer (Odocoileus virginianus) across 20 sites in the United States (Parsons et al 2017) and for sambar deer across fives sites in eastern Australia (Bengsen et al 2022). We therefore believe that sambar deer activity on camera traps is a reliable index of sambar deer relative abundance in our study areas.…”
Section: Discussionmentioning
confidence: 66%
“…We found that sambar deer activity decreased in the treatment area relative to the non-treatment area. Detection rates of deer on camera traps were positively correlated with deer densities estimated using spatial mark-resight models for white-tailed deer (Odocoileus virginianus) across 20 sites in the United States (Parsons et al 2017) and for sambar deer across fives sites in eastern Australia (Bengsen et al 2022). We therefore believe that sambar deer activity on camera traps is a reliable index of sambar deer relative abundance in our study areas.…”
Section: Discussionmentioning
confidence: 66%
“…In more densely vegetated areas, camera trap (Ramsey et al . 2019; Bengsen et al . 2022 b ), faecal DNA (Brazeal et al .…”
Section: Discussionmentioning
confidence: 99%
“…Aerial survey methods, as used in this study, are best suited to treeless or open woodland habitats (Forsyth et al 2022), such as the predominantly agricultural landscapes that we studied. In more densely vegetated areas, camera trap (Ramsey et al 2019;Bengsen et al 2022b), faecal DNA (Brazeal et al 2017) or thermal imaging surveys (T. Cox, E. O'Dwyer-Hall, R. Matthews, C. Wilsdon, D. Forsyth, A. Bengsen, G. Halverson, unpubl. data) could be used to estimate deer density (Forsyth et al 2022).…”
mentioning
confidence: 99%
“…First, the declining cost of genetic analysis means that techniques using information collected from feces, hair, and tissue to identify individuals is becoming more feasible for estimating deer abundance at management scales (Brinkman et al 2011, Brazeal et al 2017). Second, recent advances in statistical methods allow deer abundance and density to be estimated using motion‐sensitive camera images using either spatial CR (Parsons et al 2017, Macaulay et al 2020, Bengsen et al 2022) or point‐based DS (Bessone et al 2020) methods. Third, methods that identify individuals using multiple techniques, such as fecal DNA and motion‐sensitive cameras, and perform analyses using spatial CR methods (Borchers and Efford 2008, Royle and Young 2008, Royle et al 2013) are promising for providing relatively precise deer abundance estimates (Furnas et al 2020), at least for small‐ to medium‐sized study areas.…”
Section: Discussionmentioning
confidence: 99%